The effects of lower limb ischaemic preconditioning: a systematic review - French, Chloe; Robbins, Dan; Gernigon, Marie; Gordon, Dan (Frontiers in Physiology, 2024)
Ischaemic preconditioning (IPC) involves the use of repeated occlusions and reperfusions of the peripheral muscle blood supply at a limb. This systematic literature review examines the typical responses in response to the method of application during an IPC applied at the lower limb. This review focuses on the physiological responses for V ̇O2max, haemoglobin, metabolic and genetic responses to various IPC interventions. The literature search was performed using four databases and assessed using the PRISMA search strategy and COSMIN to assess the quality of the articles. Seventeen articles were included in the review, with a total of 237 participants. While there is variation in the method of application, the average occlusion pressure was 222 ± 34 mmHg, ranging from 170 to 300 mmHg typically for 3 or 4 occlusion cycles. The distribution of this pressure is influenced by cuff width, although 8 studies failed to report cuff width. The majority of studies applies IPC at the proximal thigh with 16/17 studies applying an occlusion below this location. The results highlighted the disparities and conflicting findings in response to various IPC methods. While there is some agreement in certain aspects of the IPC manoeuvre such as the location of the occlusion during lower limb IPC, there is a lack of consensus in the optimal protocol to elicit the desired responses. This offers the opportunity for future research to refine the protocols, associated responses, and mechanisms responsible for these changes during the application of IPC.